An Overview of Southern Bohemian Hilltop Settlements from Prehistory to the Late Middle Ages - Hložek, Josef; Menšík, Petr; Procházka, Milan (Archaeologia Lituana, 2018)
[full article, abstract in English; abstract in Lithuanian] The Southern Bohemian Region belongs to regions where many hilltop settlements had been built since the Early Stone Age. However, the first fortified systems were built in the Late Bronze Age, as hilltops, mountain peaks, and promontories were fortified using complex systems of ramparts and ditches. This phenomenon thereafter continued into younger prehistoric periods, especially the Early Iron Age, resulting in the foundation of hilltops in the Early Middle Ages, starting with the 9th century and frequently continuing in the form of castles and manor houses built in the Middle Ages and the Modern Period. This paper is not only an attempt to summarize and survey the use of hilltop sites and the continuity of settlements but also an effort to state their classification, characteristics, and function considering their practical, social and symbolical roles, which can be detected in both prehistoric (sophisticated fortifications with no practical use, relocation) and medieval (show of power, the question of defence) heritage.